2018
DOI: 10.1002/jcp.27202
|View full text |Cite
|
Sign up to set email alerts
|

Successful isolation and ex vivo expansion of human mesenchymal stem/stromal cells obtained from different synovial tissue‐derived (biopsy) samples

Abstract: Mesenchymal stromal cells (MSC) isolated from synovial tissues constitute a novel source of stem-like cells with promising applications in cartilage regeneration and potentially in other regenerative medicine and tissue-engineering settings. Detailed characterization of these cells is lacking, thus compromising their full potential. Here we present the detailed characterization of the ex vivo expansion of synovium-derived stromal cells collected by three different biopsy methods: synovium-direct biopsy, arthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 58 publications
3
18
0
2
Order By: Relevance
“…Mesenchymal stromal cells (MSC) have been receiving great interest in clinical settings due to their self‐renewal capacity, differentiation potential, and immunomodulatory and regenerative properties . By using the minimal criteria proposed by the International Society for Cellular Therapy (ISCT), MSC have been isolated from different human tissues, including bone marrow (BM), adipose tissue (AT), synovial membrane, periosteum, umbilical cord matrix (UCM), placenta, and amniotic fluid . Numerous studies have shown that MSC isolated from different sources present different biological features, such as distinct expression of cell surface markers, proliferative capacity, differentiation ability, and immunomodulatory and regenerative features …”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stromal cells (MSC) have been receiving great interest in clinical settings due to their self‐renewal capacity, differentiation potential, and immunomodulatory and regenerative properties . By using the minimal criteria proposed by the International Society for Cellular Therapy (ISCT), MSC have been isolated from different human tissues, including bone marrow (BM), adipose tissue (AT), synovial membrane, periosteum, umbilical cord matrix (UCM), placenta, and amniotic fluid . Numerous studies have shown that MSC isolated from different sources present different biological features, such as distinct expression of cell surface markers, proliferative capacity, differentiation ability, and immunomodulatory and regenerative features …”
Section: Introductionmentioning
confidence: 99%
“…One of the other aspects of the definition of MSCs offered by the ISCT is the differentiation potential of the cells into osteocytes, adipocytes, and chondrocytes in vitro. Synovium-derived MSCs have been shown to differentiate into these three cells [6, 49, 50]. Although Alt et al [46] found that fibroblasts exhibited no differentiation potential, other studies have shown that fibroblasts do possess the potential to differentiate into osteocytes, adipocytes, and chondrocytes [45, 47, 51].…”
Section: Introductionmentioning
confidence: 99%
“…Located within the synovial intima and sub-intima lie distinct MSC populations similar to IFP-MSC, with an origin still debated ( Li et al, 2019 ; Sivasubramaniyan et al, 2019 ). Though not populous within the tissue, these cells maintain high proliferative capacity and can differentiate into osteoblasts, adipocytes, and chondrocytes in vitro ( Ferro et al, 2019 ). The origin of synovium-derived MSC (sMSC) in the synovial lining is still not fully defined, with groups supporting the notion of MSC infiltrating from resident vasculature or even from the neighboring bone marrow.…”
Section: Ifp/synovium As a Source Of Msc For Cell Therapymentioning
confidence: 99%